2019
DOI: 10.1097/01.ju.0000555627.14712.18
|View full text |Cite
|
Sign up to set email alerts
|

Mp24-02 clinical Utility of Confirmmdx for Prostate Cancer in a Community Urology Practice

Abstract: INTRODUCTION AND OBJECTIVES: DNA promoter hypermethylation (Confirm MDX) may pick up occult prostate cancer due to a field defect the tumor exerts on normal tissue. The reported negative predictive value of Confirm MDX is high, ranging from 90-96% for low and high-grade cancer, respectively. In this study, we obtained MRI on all patients with a negative Confirm MDX to correlate imaging findings. We asked whether MRI can safely be omitted in the setting of a negative Confirm MDX.METHODS: All patients with eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A later study [89] in 2019 confirmed the impact of ConfirmMDx on biopsy decisionmaking. A total of 605 men with a median PSA level of 6.8 ng/mL and previous negative biopsies were studied.…”
Section: Confirmmdx (Mdxhealth)mentioning
confidence: 91%
“…A later study [89] in 2019 confirmed the impact of ConfirmMDx on biopsy decisionmaking. A total of 605 men with a median PSA level of 6.8 ng/mL and previous negative biopsies were studied.…”
Section: Confirmmdx (Mdxhealth)mentioning
confidence: 91%